Pacific Equatorial Sea Surface Temperature Variation During the 2015 El Niño Period Observed by Advanced Very-High-Resolution Radiometer of NOAA Satellites - Seongsuk Lee; Yu Yi (Journal of Astronomy and Space Sciences, 2018)
El Niño is the largest fluctuation in the climate system, and it can lead to effects influencing humans all over the world. An El Niño occurs when sea surface temperatures in the central and eastern tropical Pacific Ocean become substantially higher than average. We investigated the change in sea surface temperature in the Pacific Ocean during the El Niño period of 2015 and 2016 using the advanced very-high-resolution radiometer (AVHRR) of NOAA Satellites. We calculated anomalies of the Pacific equatorial sea surface temperature for the normal period of 1981–2010 to identify the variation of the 2015 El Niño and warm water area. Generally, the warm water in the western tropical Pacific Ocean shifts eastward along the equator toward the coast of South America during an El Niño period. However, we identified an additional warm water region in the Niño 1+2 and Peru coastal area. This indicates that there are other factors that increase the sea surface temperature. In the future, we will study the heat coming from the bottom of the sea to understand the origin of the heat transport of the Pacific Ocean.